Direct RT-PCR amplification of SARS-CoV-2 from clinical samples using a concentrated viral lysis-amplification buffer prepared with IGEPAL-630 - Alejandro Castellanos-Gonzalez (Nature Portfolio, 2021)
Abstract The pandemic of 2019 caused by the novel coronavirus (SARS-CoV-2) is still rapidly spreading worldwide. Nucleic acid amplification serves as the gold standard method for confirmation of COVID-19 infection. However, challenges faced for diagnostic laboratories from undeveloped countries includes shortage of kits and supplies to purify viral RNA. Therefore, it is urgent to validate alternative nucleic acid isolation methods for SARS-CoV-2. Our results demonstrate that a concentrated viral lysis amplification buffer (vLAB) prepared with the nonionic detergent IGEPAL enables qualitative detection of SARS-CoV-2 by direct Reverse Transcriptase-Polymerase Chain Reaction (dRT-PCR). Furthermore, vLAB was effective in inactivating SARS-CoV-2. Since this method is inexpensive and no RNA purification equipment or additional cDNA synthesis is required, this dRT-PCR with vLAB should be considered as an alternative method for qualitative detection of SARS-CoV-2.